Mullahs and manteaus: forms of resistance in modern day Iran. - Siti Hajar Mohamed Ali. (2008)
Based on Scott’s understanding of resistance, which necessitates the analysis of hidden transcripts, this paper transposes the concept of the hidden transcripts and passive acts of resistance onto a state versus citizens setting by analyzing the passive forms of resistance in Iran using Scott’s typology of resistance. The central argument to this thesis is that there is a disparity in expectations on the extent to which the transcripts of resistance are ‘hidden’ in an autocratic society. Briefly looking at the tug-of-war between the conservatives and the reformers, this paper asserts that the reforms initiated by Khatami and other reformers were necessary for that ‘parting of curtains’ that provides the ruling mullahs a glimpse of the previously ‘hidden transcripts’ of resistance in Iran. It concludes by acknowledging Scott’s contribution to our understanding of resistance, noting the disparity between the expectations of the extent to which the transcripts of resistance are ‘hidden’ in an autocratic society and the findings of this study and suggesting reasons for this disparity.